2021
DOI: 10.1161/jaha.121.022139
|View full text |Cite
|
Sign up to set email alerts
|

Collagen‐Targeted Peptides for Molecular Imaging of Diffuse Cardiac Fibrosis

Abstract: Background Cardiac fibrosis is the excessive deposition of extracellular matrix in the heart, triggered by a cardiac insult, aging, genetics, or environmental factors. Molecular imaging of the cardiac extracellular matrix with targeted probes could improve diagnosis and treatment of heart disease. However, although this technology has been used to demonstrate focal scarring arising from myocardial infarction, its capacity to demonstrate extracellular matrix expansion and diffuse cardiac fibrosis ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Our data exemplify the possibility of fluorescence imaging to visualize atrial fibrosis by means of molecular tracers. In particular, the findings hold promising implication for right ventricular imaging (as we have previously shown 12 ), which is especially challenging given the thin nature of structures in the right heart. Notably, the right ventricle is larger in volume than its left counterpart, but has smaller mass and thinner wall, which impedes CMRI-LGE imaging.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Our data exemplify the possibility of fluorescence imaging to visualize atrial fibrosis by means of molecular tracers. In particular, the findings hold promising implication for right ventricular imaging (as we have previously shown 12 ), which is especially challenging given the thin nature of structures in the right heart. Notably, the right ventricle is larger in volume than its left counterpart, but has smaller mass and thinner wall, which impedes CMRI-LGE imaging.…”
Section: Resultsmentioning
confidence: 64%
“…Here, we describe potential optical materials to detect atrial-pericardial and interstitial fibrosis in the clinic. Importantly, we previously reported based on histological examination and rapid blood clearance sampling in mice that the peptides were not toxic 12 . However, peptides biotoxicity assessment could further benefit from whole blood biochemical analysis, analysing electrolyte levels and liver function after peptide administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, an accurate imaging technique for fibrosis analysis is desired. Recently, several studies have also shown that the use of ColI-targeted imaging probe in MR imaging can benefit the fibrosis diagnosis in Duchenne muscular dystrophy ( Murphy et al, 2021 ), nonalcoholic steatohepatitis ( Zhou et al, 2020 ), diffuse cardiac fibrosis ( Ezeani et al, 2021 ) and pancreatic cancer ( Polasek et al, 2017 ). In this study, we generated an CD fibrosis rat model to evaluate the strategy of targeting ColI for staging fibrosis in CD and to compare its efficiency with Gd-DTPA, which is a common MR imaging contrast medium.…”
Section: Introductionmentioning
confidence: 99%